Transactional information systems theory, algorithms, and the practice of concurrency control and recovery - Weikum, Gerhard (Morgan Kaufmann, 2002)
Transactional Information Systems is the long-awaited, comprehensive work from leading scientists in the transaction processing field. Weikum and Vossen begin with a broad look at the role of transactional technology in today's economic and scientific endeavors, then delve into critical issues faced by all practitioners, presenting today's most effective techniques for controlling concurrent access by multiple clients, recovering from system failures, and coordinating distributed transactions. The authors emphasize formal models that are easily applied across fields, that promise to remain valid as current technologies evolve, and that lend themselves to generalization and extension in the development of new classes of network-centric, functionally rich applications. This book's purpose and achievement is the presentation of the foundations of transactional systems as well as the practical aspects of the field what will help you meet today's challenges. * Provides the most advanced coverage of the topic available anywhere--along with the database background required for you to make full use of this material. * Explores transaction processing both generically as a broadly applicable set of information technology practices and specifically as a group of techniques for meeting the goals of your enterprise. * Contains information essential to developers of Web-based e-Commerce functionality--and a wide range of more "traditional" applications. * Details the algorithms underlying core transaction processing functionality
Includes bibliographical references (pages 791-827) and index
Keywords: COMPUTERS / Desktop Applications / Databases; COMPUTERS / Database Management / General; COMPUTERS / System Administration / Storage & Retrieval; Transaction systems (Computer systems); Técnicas de programação; Programação concorrente; Datenbanksystem; Verteiltes Datenbanksystem; Wiederherstellung -- Informatik; Transaktionsverarbeitung; Einführung